Acerca de las formas de tratamiento en los cumplidos. - Lopera Medina, Sergio Alonso (Enunciación)
In verbal interactions, speakers use different forms of addressing to socialize with their interlocutors. This article describes the forms of addressing used by speakers of a university population with regard to the speech act of compliments. To gather data, two Discourse Completion Tests (DCTs) were applied to students, employees, and professors of a public university in Medellín, Colombia. They were applied separately and at different times, and they included simulated situations of production and response of compliments of possession, appearance, and ability. For the production and response of the compliments, the results indicate that participants use pronominal forms (te, usted) (Te queda súper ese motilado), and they vosean and tutean implicitly and explicitly. They also use vocative forms (hermano, ome, mija, mami, nena, pana, viejo, bebé, linda, parce-ro) (parce, sos mero calidoso), and sometimes use the first-person singular pronoun in the production of a compliment (Eres un teso. Ojalá yo pudiera hacerlo). It is concluded that the participants use a one-word vocative with an appellative function and some with a colloquial tone (querida, gorda, parce, mijo, man, cuchín, bebé, hermano, huevón). Finally, participants not only tutean or vosean, but also use pronominal and vocative forms in the production or response of a compliment as a manifestation of affection and solidarity towards their interlocutor.